The ISCHEMIA trial: Implications for non-invasive imaging - Rakisheva, Amina; Achenbach, Stephan; Marwan, Mohamed (Anatolian Journal of Cardiology, 2020)
Coronary artery disease (CAD) is highly prevalent and constitutes the single most common cause of death worldwide. However, the diagnosis of CAD remains challenging. There are two ways to approach the diagnosis of CAD, namely (1) by a functional non-invasive stress test to detect ischemia (stress echocardiography, stress cardiovascular magnetic resonance, single-photon emission computed tomography, positron emission tomography) or (2) by imaging for stenosis visualization (coronary computed tomography angiography or invasive coronary angiography). There are also two approaches for treatment: medical treatment and revascularization. The International Study of Comparative Health Effectiveness with Medical and Invasive Approaches (ISCHEMIA) trial investigated the outcome differences of patients who had moderate to severe ischemia on stress testing and who, after CT angiography, had ruled out left main stenosis and demonstrated at least 1 coronary artery stenosis exceeding 50%. The patients were randomized to an initially conservative treatment versus immediate revascularization. No difference in hard outcomes was found, but angina relief was more effective in the revascularization group. In this article, we explore the implications of the ISCHEMIA trial for non-invasive testing in suspected CAD.
CRIS-Team WoS Importer:2020-07-24